Sucrose Consumption Alters Serotonin/Glutamate Co-localisation Within the Prefrontal Cortex and Hippocampus of Mice - Beecher, Kate; Wang, Joshua; Jacques, Angela; Chaaya, Nicholas; Chehrehasa, Fatemeh; Belmer, Arnauld; Bartlett, Selena E. (Frontiers in Molecular Neuroscience, 2021)
The overconsumption of sugar-sweetened food and beverages underpins the current rise in obesity rates. Sugar overconsumption induces maladaptive neuroplasticity to decrease dietary control. Although serotonin and glutamate co-localisation has been implicated in reward processing, it is still unknown how chronic sucrose consumption changes this transmission in regions associated with executive control over feeding—such as the prefrontal cortex (PFC) and dentate gyrus (DG) of the hippocampus. To address this, a total of 16 C57Bl6 mice received either 5% w/v sucrose or water as a control for 12 weeks using the Drinking-In-The-Dark paradigm (n = 8 mice per group). We then examined the effects of chronic sucrose consumption on the immunological distribution of serotonin (5-HT), vesicular glutamate transporter 3 (VGLUT3) and 5-HT+/VGLUT3+ co-localised axonal varicosities. Sucrose consumption over 12 weeks decreased the number of 5-HT–/VGLUT3+ and 5-HT+/VGLUT3+ varicosities within the PFC and DG. The number of 5-HT+/VGLUT3– varicosities remained unchanged within the PFC but decreased in the DG following sucrose consumption. Given that serotonin mediates DG neurogenesis through microglial migration, the number of microglia within the DG was also assessed in both experimental groups. Sucrose consumption decreased the number of DG microglia. Although the DG and PFC are associated with executive control over rewarding activities and emotional memory formation, we did not detect a subsequent change in DG neurogenesis or anxiety-like behaviour or depressive-like behaviour. Overall, these findings suggest that the chronic consumption of sugar alters serotonergic neuroplasticity within neural circuits responsible for feeding control. Although these alterations alone were not sufficient to induce changes in neurogenesis or behaviour, it is proposed that the sucrose consumption may predispose individuals to these cognitive deficits which ultimately promote further sugar intake.